1993
DOI: 10.1111/j.1471-4159.1993.tb07436.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain α‐Ketoglutarate Dehydrotenase Complex Activity in Alzheimer's Disease

Abstract: We measured the activity of the alpha-ketoglutarate dehydrogenase complex (alpha-KGDHC), a rate-limiting Krebs cycle enzyme, in postmortem brain samples from 38 controls and 30 neuropathologically confirmed Alzheimer's disease (AD) cases, in both the presence and absence of thiamine pyrophosphate (TPP), the enzyme's cofactor. Statistically significant correlations between brain pH and lactate levels and alpha-KGDHC activity in the controls were observed, suggesting an influence of agonal status on the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(101 citation statements)
references
References 52 publications
6
95
0
Order By: Relevance
“…Reagents for the enzyme assays were from Sigma. Malic enzyme, citrate synthase, f umarase, and ␣-ketoglutarate dehydrogenase were analyzed as described (Hill and Bradshaw, 1969;Hsu and Lardy, 1969;Srere, 1969;Mastrogiacomo et al, 1993) in homogenates of cell cultures obtained by harvesting cells in 1 ml sucrose, 0.32 M, or in 5% homogenates of rat striatum in sucrose, 0.32 M. Succinate dehydrogenase activity was analyzed by formation of formazan from a tetrazolium salt (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide; Kugler et al, 1988); formazan was extracted and assayed spectrophotometrically at 570 nm (Hansen et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Reagents for the enzyme assays were from Sigma. Malic enzyme, citrate synthase, f umarase, and ␣-ketoglutarate dehydrogenase were analyzed as described (Hill and Bradshaw, 1969;Hsu and Lardy, 1969;Srere, 1969;Mastrogiacomo et al, 1993) in homogenates of cell cultures obtained by harvesting cells in 1 ml sucrose, 0.32 M, or in 5% homogenates of rat striatum in sucrose, 0.32 M. Succinate dehydrogenase activity was analyzed by formation of formazan from a tetrazolium salt (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide; Kugler et al, 1988); formazan was extracted and assayed spectrophotometrically at 570 nm (Hansen et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…26 Mastrogiacomo et al measured the activity of KGDHC in postmortem brain samples from confirmed AD cases in both the presence and absence of TPP. 27 In each brain area examined, TPP produced a greater stimulatory effect on KGDHC activity in AD group as compared with the controls. The consequences of thiamine deficit were discussed also in non-CNS tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease patients who have~=20% decreased brain TDP levels (Mastrogiacomo et al, 1996) also have reduced TDP-dependent enzyme activities (Mastrogiacomo et al, 1993;Eisinger et al, 1994;Héroux et al, 1996). One of these enzymes, aKGDHC, is a rate-limiting enzyme of the citric acid cycle and decreased enzyme activities may thus lead to a slowdown of brain oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group (Mastrogiacomo et al, 1996) as well as Butterworth's group (Héroux et al, 1996) reported a 20% decrease in TDP levels in the postmortem cortex of Alzheimer' s disease patients. This might be related to the low activities of TDPdependent enzymes observed in the cortex of these patients (Mastrogiacomo et al, 1993;Héroux et al, 2006L. BETI'ENDORFF ET AL 1996.…”
mentioning
confidence: 99%